A ROS‐Sensitive Nanozyme‐Augmented Photoacoustic Nanoprobe for Early Diagnosis and Therapy of Acute Liver Failure. Issue 7 (6th January 2022) - Wu, Haibin; Xia, Fan; Zhang, Lingxiao; Fang, Chunyan; Lee, Jiyoung; Gong, Linji; Gao, Jianqing; Ling, Daishun; Li, Fangyuan
Abstract: Early diagnosis of acute liver failure (ALF) is critical for curable treatment of patients, because most existing ALF therapies have narrow therapeutic time windows after disease onset. Reactive oxygen species (ROS), which lead to the sequential occurrences of hepatocyte necrosis and the leakage of alanine aminotransferase (ALT), represent early biomarkers of ALF. Photoacoustic imaging is emerging as a powerful tool for in vivo imaging of ROS. However, high‐performance imaging probes that can boost the photoacoustic signals of the short‐lived ROS of ALF are yet to be developed, and there remains a great challenge for ROS‐based imaging of ALF. Herein, a ROS‐sensitive nanozyme‐augmented photoacoustic nanoprobe for successful in vivo imaging of ALF is presented. The deep‐penetrating photoacoustic signals of the nanoprobe can be activated by the overexpressed ROS in ALF due to the synergy between nanocatalytic bubbles generation and thermoelastic expansion. Impressively, the nanozyme‐augmented ROS imaging enables earlier diagnosis of ALF than the clinical ALT method, and the ROS‐activated catalytic activity of nanoprobe permits timely nanocatalytic therapy of ALF. Abstract : A reactive oxygen species (ROS)‐sensitive nanozyme‐augmented photoacoustic nanoprobe is developed for early diagnosis and therapy of acute liver failure (ALF). Deep‐tissue detection of ROS in early ALF is achieved by the nanoprobe due to the synergy between nanocatalytic bubble generation and thermoelastic expansion. Meanwhile, nanozymes released from the nanoprobe can catalyze ROS into O2, allowing highly efficient therapy of ALF.